Sleep bruxism and temporomandibular disorder - an analysis of the complex relationship and implications for oral (Research, Society and Development, 2023)
Objective: To conduct an integrative review on the relationships between sleep bruxism and temporomandibular disorder. Method: A literature analysis was carried out, using articles from the PubMed, Lilacs and Scielo databases, focusing on the investigation of clinical symptoms and electromyographic/electrocardiographic data. Articles published in Portuguese and English, from 2017 to 2023, with the descriptors "bruxism", "temporomandibular disorder" and "TMD symptoms" were considered. Articles published in a period shorter than the pre-established period and those that did not address the correlation between bruxism and temporomandibular disorder were excluded. Results: Research revealed a complex relationship between bruxism and temporomandibular disorder (TMD), highlighting significant implications for oral health. An analysis indicates that bruxism can be a contributing factor to the development and worsening of TMD, emphasizing the importance of an integrated approach in the treatment and prevention of problems associated with the health of the temporomandibular joint. Conclusion: This study offers significant contributions to the understanding of factors associated with sleep bruxism and temporomandibular disorder, highlighting the continued relevance of research in this field.